PENGARUH DISIPLIN DAN KINERJA TERHADAP KOMPENSASI KARYAWAN PADA PT. PP. LONDON SUMATRA INDONESIA TBK-TERAWAS INDAH PALM OIL MILL - Suyadi Suyadi (Jurnal Media Ekonomi (JURMEK), 2016)
This study examines the Effect of Discipline and Performance on Employee Compensation at PT. PP. London Sumatra Indonesia Tbk-Terawas Indah Palm Oil Mill Musi Rawas Regency. The research method used was the questionnaire method, namely the Discipline and Performance questionnaire, and the Employee Compensation questionnaire, using the SPSS 17 program. Research Analysis using the basis of multiple linear regression calculations, the value of b1 = 0.265, b2 = 0.502, and a = 9.541 then the value of a and arranged into multiple linear regression equation with the result of the regression equation is Y = 9.541 +0.265 X1 +0,502 X2. The meaning of the equation is that the constant value of 9.542 states that if the company does not carry out discipline and performance on employee compensation at PT. PP. London Sumatra Indonesia Tbk-Supervised by Beautiful Palm Oil Mill in Rantau Jaya Village, Karang Jaya District, Musi Rawas District, the compensation value is 9.541. The regression coefficient X1 of 0.265 states that each discipline variable increases by one unit while the performance variable is fixed, it will increase the compensation of the company employees by 0.265 units. The regression coefficient X2 of 0.502 states that every addition of a performance variable equal to one unit while the disciplinary variable is fixed, it will increase the compensation of company employees by 0.502 units. From the processing of the data released, the correlation coefficient value of 0.756 indicates that there is a relationship and direction between discipline and performance with employee compensation at PT. PP. London Sumatra Indonesia Tbk-Supervised by Beautiful Palm Oil Mill in Rantau Jaya Village, Karang Jaya District, Musi Rawas Regency. From the coefficient of determination table the determination coefficient value is 0.571, which means that 57.1% of discipline and performance can be explained by questions, whereas the remaining 42.9% (100% -57.1%) is explained by other factors not included in this study. From the results of the processed data obtained the value of Fcount = 44,572, then Fcount = 44,572 is greater than Ftable = 3.14. This means that Ho is rejected and Ha is accepted thus discipline and performance has a strong and significant relationship to employee compensation at PT. PP. London Sumatra Indonesia Tbk-Inspected by Beautiful Palm Oil Mill in Rantau Jaya Village, Karang Jaya District, Musi Rawas Regency.